2012
DOI: 10.1186/1749-8090-7-92
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant vitamins C, E and coenzyme Q10 vs Dexamethasone: comparisons of their effects in pulmonary contusion model

Abstract: BackgroundThe goal of our study is to evaluate the effects of antioxidant vitamins (vitamin C and E), Coenzyme Q10 (CoQ10) and dexamethasone (Dxm) in experimental rat models with pulmonary contusion (PC).MethodsRats were randomly divided into six groups. Except for the control, all subgroups had a moderate pulmonary contusion. Animals in the group I and group II received intraperitoneal saline, group III received 10mg.kg-1 CoQ10 group IV received 100mg.kg-1 vitamin C, group V received 150mg.kg-1 vitamin E, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
14
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 44 publications
(84 reference statements)
1
14
0
Order By: Relevance
“…Various and numerous free oxygen radicals and proteolytic and lipolytic enzymes cause cellular breakdown [7, 8, 26]. The lung contusion models in rats demonstrated that MDA levels increase in lung tissue as a final product of cellular membrane lipids' peroxidation [23, 27]. In our study, we found that the MDA levels were significantly higher in the contusion group than other groups.…”
Section: Discussionsupporting
confidence: 53%
See 2 more Smart Citations
“…Various and numerous free oxygen radicals and proteolytic and lipolytic enzymes cause cellular breakdown [7, 8, 26]. The lung contusion models in rats demonstrated that MDA levels increase in lung tissue as a final product of cellular membrane lipids' peroxidation [23, 27]. In our study, we found that the MDA levels were significantly higher in the contusion group than other groups.…”
Section: Discussionsupporting
confidence: 53%
“…In our study, we found that the MDA levels were significantly higher in the contusion group than other groups. Similarly, previous studies conducted with experimental lung contusion models have shown the existence of oxidative stress in the pathogenesis of contusions [23, 27]. …”
Section: Discussionmentioning
confidence: 53%
See 1 more Smart Citation
“…33 Gokce et al reported that coenzyme Q10 is the only antioxidant that is fat soluble, synthesized endogenously and is present in tissues in the active form. 34 Moreover, Turunen et al stated that coenzyme Q10 is a mediator of lipid peroxidation and an essential cofactor in the electron transport chain and a component of the lipid membranes. 16 These effects might explain the notable reduction of the apoptotic cells expressed by marked decrease of caspase 3 expression within the alveolar and inter-alveolar tissues in this study in the lungs of rats of group IV (treated with Gokce et al stated that the strong antioxidant coenzyme Q10 plays a role in membrane stabilization as it is a component of the mitochondrial electron transport chain.…”
Section: Discussionmentioning
confidence: 99%
“…Also, it inhibits lipid peroxidation by preventing a peroxidation chain reaction and/or picking up ROS. 34 Lim et al conceived that coenzyme Q10 might attenuate the release of tumor necrosis factor alpha (TNFα) through its ability to limit the membrane lipid peroxidation with its subsequent pro-inflammatory signaling. Also, being a vital component of the respiratory chain, it plays a key role in the synthesis of cellular ATP.…”
Section: Discussionmentioning
confidence: 99%